The Analysis of Danny Maccabee’s Character as Pathological Liar Seen in Just Go With It Movie - Olyvia Natashia; Iwan Iwan iwan (e-LinguaTera, 2021)
The research is aimed at showing the character of Danny Maccabee, the main character of the film Just Go with It, as a pathological liar, the factors which have made him become a pathological liar and how his character influenced his life. The material for the analysis is the movie Just Go with It, directed by Denis Dugan. The writers applied qualitative approach,and employed relevant theories of psychology. They used the scripts of the movie as the data to be analyzed. Based on the research findings, Danny is a pathological liar since he has the characteristics of being a pathological liar. In addition, Danny Maccabee has such a character due to the factors which have made him become a pathological liar and that the effect of his character as being pathological liar has influenced his social relationship with other people and disturbed his inner peace in his life